Layered Authority and Social Institutions: Reconsidering State-Centric Theory and Development Policy. (10th May 2018) - Lust, Ellen
Abstract : Political scientists, development specialists, and policymakers assume a central place for states and state action as they define problems and design solutions. They ascribe to the state dominance over all other social organizations, viewing it as pervasive and inevitably triumphant. Even scholars such as Joel Migdal, Timothy Mitchell, and James Scott, who focus on the boundaries of the state, portray the state as more organized, technologically savvy, and capable of extending its power than social counterparts, putting the latter on the defensive. Scholars and policymakers alike also have arrogated to the state the moral monopoly to pursue certain imperatives that other organizational forms can and do aspire to provide. These include providing security and protection from predation, allocating scarce resources, and arbitrating values and interests in society.